Financing social economy through wagf - تمويل الاقتصاد الاجتماعي من خلال الوقف دراسة مقاصدية شرعية - Saleh, Abdulmajid Obaid Hasan (2019)
Abstract This study aims to introducing the solidarity economy, which is considered as a modern alternative to achieve economic and social development. Heretofore, No developed or developing country can carry out all the developmental tasks in society. The research also targets at questioning the purposes of the Shari'a in the waqf and the mechanism of its application in promoting the solidarity economy, and declaring that the Waqf Foundation is considered a fertile resource for activating social solidarity projects provided by the Islamic economy to cure the imbalance in the distribution of wealth and income of human societies from the institutions